2020
DOI: 10.4102/phcfm.v12i1.2307
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to adolescents’ access and utilisation of reproductive health services in a community in north-western Nigeria: A qualitative exploratory study in primary care

Abstract: Background There is a dearth of qualitative studies exploring in-depth barriers that adolescents face in accessing and utilising reproductive health services (RHS) in Nigerian primary healthcare centres. Aim This study explored the barriers hindering adolescents’ access to and utilisation of RHS in primary healthcare centres. Setting This study was conducted in three primary healthcare centres in Kaduna North Local government area, Nigeria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 17 publications
4
44
0
Order By: Relevance
“…A study conducted in the Ashanti region of Ghana [ 26 ] also revealed that condoms (33.3%) were the most used form of contraceptive among sexually active female adolescents. We believe that the common use of condoms, a short-term method of contraception, may be because they are presumed to have no side effects and are more easily available and accessible from providers [ 38 ]. This may be particularly important in this population, where although 45% of sexually active girls used contraception, only 39% knew of a place they felt comfortable accessing it—this may limit them to seeking only the most accessible form of contraception.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the Ashanti region of Ghana [ 26 ] also revealed that condoms (33.3%) were the most used form of contraceptive among sexually active female adolescents. We believe that the common use of condoms, a short-term method of contraception, may be because they are presumed to have no side effects and are more easily available and accessible from providers [ 38 ]. This may be particularly important in this population, where although 45% of sexually active girls used contraception, only 39% knew of a place they felt comfortable accessing it—this may limit them to seeking only the most accessible form of contraception.…”
Section: Discussionmentioning
confidence: 99%
“…The SRH coverage rates in Nigeria are typically low, especially in the rural (and hard-to-reach) areas and among adolescents [17,18]. Some of the identified barriers to accessing SRH services include inadequate knowledge about the services, inconvenient health facility opening hours, remoteness of facilities, financial constraints as well as community and religious norms [19]. Wider systemic issues also impact negatively on the SRH system in Nigeria.…”
Section: The Fragile State Of Srh In Nigeriamentioning
confidence: 99%
“…Health care facilities provide an important setting for adolescents to access accurate SRH preventive information, testing and treatment services. Unfortunately, adolescents’ utilisation of these facilities has remained low due to fear of being stigmatised, negative attitudes of health care providers and a lack of age-appropriate and adolescent-centred services [ 15 , 16 ]. For example, Odo et al [ 17 ] report that, for adolescents in Enugu State, SRH services were perceived as financially inaccessible and not adolescent-friendly.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Odo et al [ 17 ] report that, for adolescents in Enugu State, SRH services were perceived as financially inaccessible and not adolescent-friendly. In many African countries, religion and social structures create certain norms around ASRH, which in turn create barriers for adolescents using these services [ 15 ]. Rather than seek health care in health facilities, some adolescents in Nigeria have reported seeking SRH care from unprofessional providers such as medicine vendors, traditional healers, and others self-medicate by purchasing drugs without prescription against the backdrop of antibiotic abuse and resistance [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%